Preloading with drugs before entry to the nighttime entertainment district: presentation, intoxication rates, and effects of police presence during assessment - Lee R. J. Hughes; Corey Allen; Grant J. Devilly (BMC, 2023)
Abstract Background Past research has either focused on alcohol or drug preloading before a night out, but not on the interaction between them. With increased risks of harm through interaction effects, we wished to build upon previous research in this area. We sought to determine who drug preloads, why do people engage in this practice, what drug/s are people using, and how inebriated they are as they enter the NED. Additionally, we examined what impact varying levels of police presence has on the collections of sensitive data in this context. Methods We captured estimates of drug and alcohol preloading from 4723 people entering nighttime entertainment districts (NEDs) in Queensland, Australia. Data collection occurred under three varying conditions of police presence (i.e., no police present, police present but not engaging with participants, and police engaging with participants). Results People who admitted to preloading drugs were found to be younger in age than non-drug admitters, more likely to be male than female, use one type of drug (mostly stimulants) rather than multiple (if we exclude alcohol), significantly more intoxicated upon arrival, and more subjectively affected from their use of alcohol and drugs as Breath Approximated Alcohol Concertation levels increased. People were more likely to admit having used drugs in the absence of police, but this had only a small effect. Conclusions People who drug preload are a vulnerable subset of the youth population that is susceptible to experiencing harms in this context. As they drink more alcohol, they experience higher affects than those who do not report to also take drugs. Police engagement through service rather than force may mitigate some risks. Further enquiry is needed to better understand those who engage in this practice and to have quick, cheap, objective tests of what drugs these people are using.